Squamous cell carcinomas in organ transplant recipients. Comparison of histopathological and clinical features of squamous cell carcinoma in patients after organ transplantation to immunocompetent patients - Renczyńska-Matysko, Joanna; Marquardt-Feszler, Adriana; Dębska-Ślizień, Alicja; Imko-Walczuk, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
The occurrence of neoplasms is one of the most common complications and second most frequent cause of death in organ transplant recipients (OTRs). The most frequently occurring neoplasms are skin cancers, predominantly squamous cell carcinoma (SCC). However, the ratio between SCC and basal cell carcinoma (BCC) in OTRs differs in several studies depending on the follow-up time, country, environment and other factors. In this population SCC has a more aggressive course with the presence of metastases and tends to have multifocal growth. The clinical and histopathological picture of SCC in OTRs differs from that observed in immunocompetent patients, which implicates tumour treatment and prognosis. The clinical features and distinctness which pertain to SCC in post-transplantation patients are described in this paper.